KEABSAHAN KONTRAK BERJANGKA PADA PLATFORM BINOMO - Shakira Elagemda; Nuzul Rahmayani; Jasman Nazar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The development and progress of technology is very rapid, making everything now easier, including accessing the internet. The economy is one of the many fields that are experiencing rapid development as a result of technological developments, investment is no exception. One investment that is currently being discussed is the binomo platform. But in reality, binomo is not an investment but a platform that provides binary options services for potential investors. Juridically, the validity of futures contracts on the Binomo platform contradicts several articles in the Civil Code. The purpose of the research is to understand how the validity of futures contracts on the binomo platform is reviewed from the Civil Code. The research method is normative juridical research, namely research that is only aimed at written regulations, so this writing is closely related to libraries, because it will require secondary data from libraries that support the subject matter discussed and the laws and regulations. The results of the study, the validity of the futures contract on the binomo platform in terms of the Civil Code is contrary to several articles in the Civil Code, when referring to the legal terms of the agreement in article 1320 of the Civil Code, binomo does not meet when viewed from the 3rd legal requirement, namely a certain thing and the third legal requirement. 4, namely the legal causes of law.